BASIC INVESTMENT TRAINING IN THE CAPITAL MARKET FOR UMKM AND RESIDENTS OF HAGU BARAT LAUT VILLAGE - Muhammad Multazam; Rico Nur Ilham; Ayu Anora; Muttaqien; Rahmiatul Aula; Ismuhadi; Utaminingsih, Eka (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
Low financial literacy and access to investment information among MSMEs and rural communities are challenges in realizing financial inclusion in Indonesia. This study aims to evaluate the effectiveness of basic investment training in improving capital market literacy for MSMEs and residents of Gampong Hagu Barat Laut. The method used is a descriptive quantitative approach with a one-group pretest-posttest design, involving 45 participants. The results of the analysis showed a significant increase in investment literacy scores from an average of 42.6 to 73.1 (p <0.001), covering aspects of knowledge, attitudes, and understanding of risk. The conclusion of this study shows that community-based training is effective in improving investment literacy, and needs to be replicated in other areas as a local-based financial inclusion strategy.